(untitled) (Research, Society and Development, 2021)
Citriculture has considerable economic and social importance in Brazil, and the quality of the citrus groves is directly related to the rootstock used. Trifoliate orange [Poncirus trifoliata (L.) Raf.] has been shown to be a good rootstock, being used in Brazil in the southern region of the country. The objective was to evaluate the growth of trifoliate orange seedlings and the dry matter yield of shoot and roots in two soil layers as affected by lime and agricultural gypsum doses. Trifoliate orange seedlings were grown columns of PVC pipe, with dimensions of 15 × 35 cm (diameter × length). The columns were sectioned in two rings: upper (15 cm high) and lower (20 cm high) rings. The experimental design was in randomized blocks with four replications, arranged in a factorial scheme (2×4)+1, with two liming treatments and four doses of agricultural gypsum (both applied only in the soil of the upper ring), and an additional treatment (with liming application in the soil of both rings). Liming and doses of gypsum did not affect the shoot growth of the trifoliate orange seedlings, however there was a higher chlorophyll content at 55 days after transplanting (DAT) with gypsum application without liming. Liming increased the yield of root dry matter in the superficial layer (0-15 cm deep), showing the importance of correcting soil acidity for adequate development of root system in trifoliate orange seedlings.